Results of dental examination of children with obstructive sleep apnea syndrome - Drohomyretska, Мирослава Стефанівна; Gergel , Ірина (Actual Dentistry, 2023)
Introduction. Obstructive apnea syndrome is a widespread pathology. According to researchers, more than 1 billion people worldwide suffer from this pathology, most of whom are undiagnosed and unaccounted for. One or another degree of OSAS with existing symptoms in 8-16% of adults. OSAS occurs 4 times more often in men and 7 times more often in obese people. Genetic susceptibility or a heavy family history of OSAS, as well as craniofacial anatomical abnormalities that lead to narrowing of the upper airways, may confer a higher risk of OSAS.he prevalence of OSAS in children is 1–5%, the peak incidence is determined between the ages of 2 and 6 (2.5 years for boys and 4 years for girls). The search for an effective solution to the relationship between the problem of obstructive sleep apnea and bite pathology is an extremely urgent and unsolved problem of modern dentistry and should be solved by a combination of complex rehabilitation of patients by specialists of various profiles. Goal. Assessment of the dental status of 233 patients aged 6–18 years with obstructive sleep apnea syndrome (OSAS). Research methods. Surveys, questionnaires using the BEARS screening questionnaire and a questionnaire to detect clinical signs of stomatognathic system disorders and bruxism in children, primary examination, clinical (including visualization with maximum opening of the mouth - Mallampati test); dental (determining occlusal contacts using a dental copier and photographing them for further analysis, and making BruxChecker dental thermoformed plates) and laboratory (studying diagnostic models in the articulator), statistical processing of the obtained results. The results. The TRH study of children with OSAS showed obstruction of the respiratory tract at different levels: nasopharynx, oropharynx, and larynx. Depending on the age group, the levels of obstruction differed significantly. In the 1st age group (6–12 years), narrowing of the respiratory tract at the level of the nasopharynx was found in 65.1%, at the level of the oropharynx – in 17.7%, at the level of the larynx – in 10.3% of children. The combination of airway narrowing at the level of the nasopharynx and larynx was determined in 6.9% of children. In adolescents aged 13–18 (II age group), airway obstruction at the level of the nasopharynx was determined in 10.3%, and combined at the level of the oropharynx and larynx – in 89.7%. Conclusions. The main principle in the diagnosis of OSA is the need to take a detailed history of life and disease, followed by a comprehensive physical examination, including an orthodontic examination to detect dental and jaw pathology, and treatment should be carried out through a multidisciplinary approach involving various specialists.